Residential trajectories in Lisbon Metropolitan area: an exploratory approach - Pereira, S. M.; Bringé, A.; Ferreira, A. (CIDADES, Comunidades e Territórios, 2014)
The metropolization process of Lisbon began in the 50’s and reached its greatest intensity over the following two decades. Nowadays, the Lisbon Metropolitan Area (LMA) has almost 3 million inhabitants and the city of Lisbon has about 550 thousand. In order to have a deeper understanding of the development logics of this territory over the last 60 years, this paper analyses the residential trajectories of LMA inhabitants who were born between 1945-1975. The analysis was carried out using a longitudinal approach that, in contrast to the traditional transversal ones, emphasizes the diachronic aspects by reconstituting the residential biography of each respondent in the survey (N=1500), which was implemented during the second half of 2011. The research underlies three essential dimensions of residential trajectories: 1) location and geographical direction; 2) the housing model that is directly related to the morphology of the territories; 3) the property regime, which is of profound interest in the current Portuguese context because of the economic crisis that is diminish the propensity for homeownership. Due to the plethora of data, this paper will focus on the first dimension with two purposes: 1) to identify the dominant trajectories (e.g.: countryside-periphery, Lisbon centre-periphery, periphery-periphery, etc.); 2) to discuss the various sociological profiles of the protagonists in each of those dominant trajectories, in order to understand the multiple combinations and intersections of variables (social class, generation, household type), which characterize and differentiate each other.